Rancang Bangun Sistem Informasi Penerimaan Peserta Didik Baru Berbasis Web di Sekolah Dasar Negeri Marawang - Angelina Malo; Adelbertus Umbu Janga; Maria Wilda Malo (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
This research aims to design and build a web-based New Student Admission Information System (PPDB) at Marawang State Elementary School. This system was developed as a solution to improve efficiency, transparency, and accuracy in the process of admitting new students. By utilizing web-based technology, prospective students and parents can register online, upload required documents, and monitor registration status in real-time. The school has the convenience of verifying data, managing information, and generating admission reports automatically. Data security is an important aspect of this system, so it is designed with personal information protection features to maintain the confidentiality of students. The system development method is carried out through a web-based approach that allows flexible access from a variety of devices. The results of the study show that the web-based PPDB system is able to speed up the administration process, reduce manual errors, and increase user satisfaction. The implementation of this system not only provides benefits for Marawang State Elementary School, but can also be used as a model for other schools in adopting a similar information system. Thus, the web-based PPDB system contributes to the modernization of basic education management and supports the creation of more effective and transparent educational services.